Algorithmic assemblages of care: imaginaries, epistemologies and repair work. (10th October 2019) - Schwennesen, Nete
Abstract: In the past decade, the figure of the algorithm has emerged as a matter of concern in discussions about the current state of the healthcare sector and what it may become. While analytical focus has mainly centred on 'algorithmic entities', the paper argues that we have to move our analytical focus towards 'algorithmic assemblages', if we are to understand how advanced algorithms will affect health care. Departing from this figure, the paper explores how an algorithmic system, designed to 'take on' the role of a physiotherapist in physical rehabilitation programmes in Denmark, was designed and made to work in practice. On the basis of ethnographic fieldwork, it is demonstrated that the algorithmic system is a fragile accomplishment and outcome of negotiations between the imaginaries embedded in its design and the ongoing adjustments of IT workers, patients and professionals. Drawing on recent work on the fragility and incompleteness of algorithms, it is suggested that the algorithmic system needs to be creatively 'repaired' to build and maintain enabling connections between bodies in‐motion and professionals in arrangements of care. The paper concludes by addressing accountability for the workings of algorithmic systems in medical practice, suggesting that such questions must also be discussed in relation to encounters between algorithmic imaginaries, health professionals and patients, and the various forms of 'repair work' needed to enable algorithmic systems to work in practice. Such acts of accountability cannot be understood within an ethics of transparency, but are better thought of as an ethics of 'response‐ability', given the need to intervene and engage with the open‐ended outcomes of algorithmic systems.